2018
DOI: 10.1002/pon.4942
|View full text |Cite
|
Sign up to set email alerts
|

Everyday protective buffering predicts intimacy and fear of cancer recurrence in couples coping with early‐stage breast cancer

Abstract: Objective: Patient and spouse/partner mutual self-disclosure is central for maintaining intimacy and cognitive processing when transitioning to life after cancer.Protective buffering inhibits self-disclosure and is defined as efforts to protect one's partner from upset and burden by hiding or denying cancer-related concerns. Intimacy and fear of cancer recurrence (FCR) are important determinants of individual and couple adaptation following cancer. Links between protective buffering and intimacy have not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
60
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 34 publications
(51 reference statements)
3
60
0
Order By: Relevance
“…Incentive structures also likely vary. However, in general, the completion rates fell within the ranges reported by other research teams [ 37 ], in some cases higher by 8% to 14% [ 38 - 40 ] and in other cases lower by 4% to 7% [ 41 ]. These differences may, in part, be explained by differences in numbers of items, for example, the battery was somewhat longer than that described by Perndorfer et al [ 41 ].…”
Section: Discussionsupporting
confidence: 76%
“…Incentive structures also likely vary. However, in general, the completion rates fell within the ranges reported by other research teams [ 37 ], in some cases higher by 8% to 14% [ 38 - 40 ] and in other cases lower by 4% to 7% [ 41 ]. These differences may, in part, be explained by differences in numbers of items, for example, the battery was somewhat longer than that described by Perndorfer et al [ 41 ].…”
Section: Discussionsupporting
confidence: 76%
“…Our assumptions suggested relationships between illness representations of breast cancer survivors' and their spouses and couple communication (between‐person level), which was enlightened by a series of relevant previous studies . On the basis of prior research about couple communication and daily FCR, our assumptions also suggested how the daily exchanges of positive or negative content are associated with variation of FCR as experienced in daily life (within‐person level). To be specific, we hypothesized that (a) breast cancer survivors' and their spouses' negative illness representations are negatively associated with their levels of disclosures of positive and negative information at the between‐person level, (b) that breast cancer survivors' and their spouses' disclosures of negative and positive information predict increases or decreases in the partner's perceptions of negative and positive information at the within‐person level across 30 time points of 10 days, and (c) that negative or positive perceptions of breast cancer survivors' and their spouses' are predictive of their daily fluctuations in FCR at the within‐person level across 30 time points of 10 days.…”
Section: Introductionmentioning
confidence: 69%
“…Furthermore, in one study, intimate couple communication in daily life was found to relieve stress and even reduce the risk of disease such as upper respiratory infection . Recent daily diary studies also showed that hiding or denying cancer‐related concerns was associated with decreased intimacy and increased daily FCR among breast cancer patients and their spouses, while responsiveness between breast cancer patients and their spouse after the mammogram was associated with lower daily FCR . Thus, it seems likely that supportive couple communication can reduce the couple's FCR, while the failure to interact in supportive ways may maintain or increase FCR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregivers who are not related to the patient represent a small but different caregiver group with unique communication patterns that may not be as open, a known predictor of the quality of dyadic communication 11,24 . For example, cancer patient‐spousal caregiver dyads often engage in protection behaviors in which partners abstain from discussion of certain topics to try to mitigate distress 25,26 . This may not happen among patient‐friend caregiver dyads.…”
Section: Discussionmentioning
confidence: 99%